PREDICTING PERCEIVED COMPLEXITY USING LOCAL CONTRAST STATISTICS AND FRACTAL INFORMATION - KACHA, L.; MATSUMOTO, N.; MANSOURI, A.; CAVALCANTE, A. (Courrier du Savoir, 2014)
This study aims to explore visual complexity in streetscape composition using RMS contrast information and Fractal Analysis. The dataset was composed of 74 streetscape images, taken in Algeria and Japan in daytime and nighttime. The evaluation and analysis covered two phases: (1) Subjective quantification of perceived complexity using ranking method. (2) Visual complexity measurement based on RMS contrast statistics and fractal characteristics of the streetscape images. The results showed a positive correlation between the subjective ranking of complexity in streetscape images and the proposed measure of visual complexity “α” as well as with the fractal dimension Db